Notions of home for diasporic Muslim women writers - Abdul Manaf, Nor Faridah; Hashim, Ruzy Suliza (EuroJournals Publishing, Inc., 2009)
Literatures on Muslim women writers living in a new land are scarce and rarely discussed. This paper aims to explore the writings by two Muslim women writers who had to leave their countries for various reasons but "returned home" through their creative work, exemplifying the diasporic notion of being ambivalent and critical of their 'homelands' (and possibly also of their 'hostlands').By scrutinising the works by Azar Nafisi, Reading Lolita in Tehran and Mohja Kahf, The Girl in the Tangerine Scarf, we will demonstrate an aspect of unsettling women and problematise the notion of 'home' for both writers. Both Nafisi and Kahf have a different way of putting forth issues relating to home but very often, politicising much of the issues raised in their attempts to address matters relating to justice and women's participation in the public domains. By investigating their notions of home, we will be able to draw some conclusions about what memories and political (read: religious) concerns they evoke and how their recollections sketch pictures of the home they no longer call their own.